PENGARUH BRAND EQUITY, BRAND IMAGE DAN CONSUMER SATISFACTION TERHADAP REPURCHASE INTENTION BRAND X DI TANGERANG - Chandra, Gillian Emery; Yusrin, Nur Amalyna (Publika Citra Media, 2025)
This study aims to analyze the influence of Brand Equity, Brand Image, and Consumer Satisfaction on Repurchase Intention. The research was conducted using a quantitative method, where data were collected through questionnaires distributed to respondents in Tangerang. The data analysis method used was Structural Equation Modeling (SEM) with SmartPLS 3.1 software. The results of this study found that Brand Equity, Brand Image, and Consumer Satisfaction collectively have a significant influence on Repurchase Intention. These findings indicate that an increase in brand equity, a positive brand image, and consumer satisfaction can drive customers' repurchase intention for Brand X products. The implications of this study highlight the importance of strategies to strengthen brand equity, improve brand image, and manage consumer satisfaction to ensure loyalty and sustain repurchase intentions.